Doxorubicin‐induced heart failure in cancer patients: A cohort study based on the Korean National Health Insurance Database. (19th November 2018) - Kim, Young Ae; Cho, Hyunsoon; Lee, Nayoung; Jung, So‐Youn; Sim, Sung Hoon; Park, In Hae; Lee, Sunmi; Lee, Eun Sook; Kim, Hak Jin
Abstract: Background: Doxorubicin is a typical anticancer drug that causes cardiomyopathy and heart failure (HF). The aim of our study was to investigate incidence, risk factors for doxorubicin‐induced HF in Korean cancer patients and their survival rate, utilizing a nationwide population‐based cohort. Methods: We analyzed 58 541 cancer patients who received doxorubicin between 2003 and 2010. Descriptive analysis was performed in patients with breast cancer, hematologic malignancy, gynecological malignancy, and sarcoma. Risk factors associated with doxorubicin‐induced HF were investigated using a Cox proportional hazards model. The survival rate of doxorubicin‐induced HF patients was compared with that of patients without doxorubicin‐induced HF. Results: A total of 2324 (4%) were diagnosed with doxorubicin‐induced HF. In patients with breast cancer, predictive risk factors for doxorubicin‐induced HF included age over 65 years [hazard ratio (HR) 1.34, 95% confidence interval (CI) 1.05‐1.72], hypertension [HR 2.45 (2.12‐ 2.84)], diabetes mellitus [HR 1.26 (1.05‐1.51)], coronary artery disease [HR 2.08 (1.63‐2.66)], advanced stage [HR 1.31 (1.13‐1.50)], and trastuzumab administration [HR 2.94 (2.54‐3.40)]. In patients with hematologic malignancy, predictive risk factors included age over 65 years [HR 1.75 (1.49‐2.07)], hypertension [HR 1.62 (1.37‐1.92)], and coronary artery disease [HR 2.28 (1.80‐2.89)]. Five‐year survival rates of patients with doxorubicin‐induced HF were significantly lower relative to those of patients without HF in breast cancer and hematologic malignancy: 80% vs 84% and 69% vs 75%, respectively ( P  < 0.001). Conclusions: In cancer patients treated with doxorubicin, management of risk factors, early detection, and treatment for doxorubicin‐induced HF might be critical for patient survival. Abstract : In cancer patients treated with doxorubicin, management of risk factors, early detection, and treatment for doxorubicin‐induced HF might be critical for patient survival. Because the data from Asian population in terms of cardio‐oncology are scarce, our study tried to fill that gap.